Harnessing natural killer cell-mediated immune responses in obesity-associated cancer - Mylod, Eimear (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2023)
Oesophagogastric adenocarcinomas (OAC) encompass a group of inflammation-driven and obesity-associated cancers. Poor 5-year survival rates of less than 20% and treatment response rates of less than 30% place these as poor prognosis cancers, in urgent need of new therapeutic options. As immunotherapy emerges as the fourth pillar of cancer treatment and immune dysregulation in OAC has been uncovered, we propose that novel immunotherapeutic approaches can improve treatment efficacy and outcomes in the growing number of OAC patients. Natural killer (NK) cells are lymphocytes of the innate immune system which function as cytotoxic mediators and key cytokine producers. However, NK cells are severely dysregulated in obesity with phenotypic and functional alterations compromising their anti-tumour abilities. Furthermore, a number of studies have shown that low infiltration of NK cells into solid tumours is associated with poorer prognosis. Therefore, NK cell-based immunotherapies hold great promise to overcome immune dysfunction in cancer. However, two key issues are known to compromise their efficacy: namely successful infiltration of solid tumours and the immunosuppressive tumour microenvironment (TME). In the context of OAC, we have reported active recruitment of NK cells to extratumoural tissues namely the omentum and believe that this compromises their infiltration of the tumour. We have previously reported that sucherroneous migration is mediated by the Fractalkine:CX3CR1 axis and propose that CX3CR1 antagonism may be employed to limit this. In this thesis, we have explored the therapeutic applicability of CX3CR1 antagonism to boost NK cell infiltration of tumours in OAC. We have profiled NK cells in OAC patient-derived blood, omentum and tumour samples unearthing unique phenotypes within these compartments and identifying immune dysregulation in the most viscerally obese OAC patients. Importantly, we have identified that the frequencies of intratumoural NK cells are lowest in the most viscerally obese OAC patients, highlighting how detrimental visceral obesity is for anti-tumour immunity in these patients. Furthermore, we have explored the impact of the soluble microenvironments of adipose and tumour tissues derived from viscerally obese and non-obese OAC patients and unveiled divergent effects of these microenvironments on NK cell phenotype and function. Interestingly, our data have revealed that the obese TME impairs NK cell cytotoxicity, thus emphasising the importance of immunotherapeutic approaches to overcome immunosuppressive signalling in OAC. Fractalkine has been previously reported as a driver of obesity-association inflammation, both by our group and others. Our group have previously reported that fractalkine is a key driver of NK and CD8+ T cell migration to the omentum in OAC and uncovered its non-chemotactic effects on CD8+ T cells. Here, we examined the effects of physiologically relevant levels of fractalkine on the phenotype and function of NK cells. Our data revealed that fractalkine mediates the endocytosis of CX3CR1 on the surface of NK cells, increased CD27 expression and shifts NK cell phenotype towards a pro-inflammatory cytokine profile, thus further implicating this chemokine in the potentiation of omental inflammation in obesity. Furthermore, we identified a role for fractalkine in antagonising IL-15-mediated activation of NK cells, highlighting the potential multi-faceted benefits that CX3CR1 antagonism could confer in OAC. Finally, in this thesis, we have developed a novel OAC patient-derived ex vivo model to study immune cell migration between different tissue compartments. Using this platform our data showed that when simultaneously exposed to the chemotactic cues of OAC patient-derived omentum and tumour, NK cells preferentially migrate towards the soluble chemotactic cues of the omentum. Furthermore, when pre-treated with the CX3CR1 antagonist E6130, such migration could be skewed towards the tumour and away from the omentum. In addition, by remodelling the tumour compartment using alternative NK cell chemokines, NK cell migration could be skewed towards tumour and away from the omentum. These proof-of-concept studies have shown that CX3CR1 antagonism, together with remodelling the chemokine profile of the OAC TME, can be used to limit migration towards the omentum and boost migration towards the tumour. These data pave the way for further development of chemokine-targeted therapies in OAC. Overall, this study has identified NK cell dysregulation in obese OAC patients, emphasising that the growing prevalence of obesity in cancer patients must be considered when designing NK cell-based immunotherapies. Furthermore, we have uncovered the therapeutic utility of CX3CR1 antagonism to enhance anti-tumour immunity in OAC and its potential extension to other obesity-associated malignancies. Finally, we have developed a novel model of immune cell decision making and migration in OAC which has applicability beyond OAC and will facilitate future bench-top pre-clinical testing of chemokine-based immunotherapies.
APPROVED
Keywords: NK Cell; Oesophageal Cancer; Chemokine; Immunology